Impact of ethnicity and extreme prematurity on infant pulmonary function. Issue 7 (30th September 2013) - Hoo, Ah‐Fong; Gupta, Amit; Lum, Sooky; Costeloe, Kate L.; Huertas‐Ceballos, Angela; Marlow, Neil; Stocks, Janet
Summary The impact of birth before 27 completed weeks of gestation on infant pulmonary function (PF) was explored in a multi‐ethnic population in comparison to more mature preterm controls (PTC) and healthy fullterm infants. Plethysmographic lung volume (FRCpleth) and forced expired volume (FEV0.5) were obtained at ∼12 months post‐term age in 52 extremely preterm (EP) infants (median [range] gestational age [GA]: 26 [23–27] weeks; 40% White mothers; 79% with BPD), 41 PTC (GA:35 [30–36] weeks; 37% White mothers) and 95 fullterm infants (GA:40 [37–42] weeks; 86% White mothers). Using reference equations based on identical equipment and techniques, results were expressed as z‐scores to adjust for age, sex and body size. FEV0.5 was significantly lower in EP infants when compared with PTC (mean difference [95% CI]: −1.02[−1.60; −0.44] z‐scores, P < 0.001), as was forced vital capacity (FVC) but there were no significant differences in FRCpleth or FEV0.5/FVC ratio. FEV0.5, FVC, and FEV0.5/FVC were significantly lower in both preterm groups when compared with fullterm controls. On multivariable analyses of the combined preterm dataset: FEV0.5 at ∼1 year was 0.11 [0.05; 0.17] z‐scores higher/week GA, and 1.28 (0.49; 2.08) z‐scores lower in EP infants with prior BPD. Among non‐white preterm infants, FEV0.5 was 0.70 (0.17; 1.24) z‐scores lower, with similar reductions in FVC, such that there were no ethnic differences in FEV0.5/FVC. Similar ethnic differences were observed among fullterm infants. These results confirm the negative impact of preterm birth on subsequent lung development, especially following a diagnosis of BPD, and emphasize the importance of taking ethnic background into account when interpreting results during infancy as in older subjects. Pediatr Pulmonol. 2014; 49:679–687. © 2013 Wiley Periodicals, Inc.